II-04 Bone marrow mesenchymal stem cells from patients with SLE maintain an interferon signature during in vitro culture. (August 2018) - Gao, Lin; OConnell, Mary; Allen, Maria; McDavid, Andrew; Anolik, Jennifer H; Looney, Richard J
Abstract : Background: We have previously shown that SLE BMSCs have a pro-inflammatory mediated by a MAVS and IFNβ feedback loop. Compared to healthy controls, SLE BMSCs produced increased amounts of IFNβ and had increased mRNA for several genes induced relatively specifically by IFNβ. They also had decreased proliferation, increased ROS, increased DNA damage and repair (DDR), a senescence associated secretory phenotype, and increased senescence-associated β-galactosidase. To better understand the phenotype of SLE BMSCs we conducted RNA sequencing. Methods: Patients fulfilling SLE classification criteria and age and sex matched healthy controls were recruited under an Institutional Review Board approved protocol (6 pairs). Bone marrow aspirates and peripheral blood samples were obtained. BMSCs were isolated with low density Ficoll/Hypaque and grown in tissue culture. Purity of BMSC cultures were verified by flow cytometry. Early passage BMSC were harvested and mRNA samples were sent for RNAseq through the University of Rochester Genomics Core. Serum samples with assayed for IFNβ using an ELISA from PBL. Results: Hierarchical clustering of normalized RNAseq profiles found SLE patients with high levels of serum IFNβ (>13 units per XXX) grouped together while SLE patients with low levels of IFNβ grouped together with healthy controls. Principal component analysis found the majority of the variance could be explained by PC1 (32.3%) and PC2 (25.5%). While PC1 did not separate SLE or SLE IFNβ high from the other samples, PC2 clearly differentiated SLE IFNβ high samples from SLE IFNβlow and control samples. SLE IFNβ low and control sample overlapped in both PC1 and PC2. The top upregulated genes in PC2 were RSAD2, MX1, IFIT1, IFIT2, OAS1, CMPK2, OASL, IFIT3, ISG15, IDO1, IFI6, MX2, HERC5, and IFIH1 … all type I interferon-induced genes. Conclusions: BMSCs from SLE patients are heterogeneous. A subgroup of SLE BMSC are distinguished from other SLE BMSC and from controls by increased levels of mRNAs induced by type I interferons. Moreover, SLE BMSC with increased levels of mRNA for type I interferon-induced genes when grown in vitro are derived from patients with increased levels of IFNβ in vivo . Acknowledgements: This work was supported in part by a grant from the Lupus Research Alliance.